Comparison of Macitentan and Bosentan on Right Ventricular Remodeling in a Rat Model of Non-vasoreactive Pulmonary Hypertension. Issue 5 (November 2015) - Iglarz, Marc; Landskroner, Kyle; Bauer, Yasmina; Vercauteren, Magali; Rey, Markus; Renault, Berengère; Studer, Rolf; Vezzali, Enrico; Freti, Diego; Hadana, Hakim; Schläpfer, Manuela; Cattaneo, Christophe; et al.
Abstract : Aims: We compared the efficacy of macitentan, a novel dual endothelin A/endothelin B receptor antagonist, with that of another dual endothelin receptor antagonist, bosentan, in a rat model of non-vasoreactive pulmonary hypertension (PH) with particular emphasis on right ventricular (RV) remodeling. Methods and Results: Unlike monocrotaline or hypoxic/sugen rats, bleomycin-treated rats presented a non-vasoreactive PH characterized by the absence of pulmonary dilatation to adenosine. We therefore chose the bleomycin rat model to compare the effects of the maximally effective doses of macitentan and bosentan on pulmonary vascular and RV remodeling. Macitentan (100 mg·kg −1 ·d −1 ), but not bosentan (300 mg·kg −1 ·d −1 ), significantly prevented pulmonary vascular remodeling, RV hypertrophy, and cardiomyocyte diameter increase. Cardiac protection by macitentan was associated with a significant attenuation of genes related to cell hypertrophy and extracellular matrix remodeling. Microautoradiography and high performance liquid chromatography analysis showed greater distribution of macitentan than bosentan in the RV and pulmonary tissue. Conclusions: Macitentan was more efficacious than bosentan in preventing the development of pulmonary and RV hypertrophies in a model of non-vasoreactive PH. Greater ability to distribute into the tissue could contribute to the greater structural improvement by macitentan compared with bosentan. Abstract : Supplemental Digital Content Is Available in the Text.